Strategy formulation for accelerating safe sanitation improvement in Lamongan - Dinar Dwi Andhi; Yulfiah Yulfiah (Center for Science and Technology, Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Meeting the national sanitation target is a significant challenge for Lamongan Regency. This research aims to formulate strategies to accelerate the improvement in sanitation access in order to exceed national targets. A mixed-methods approach was employed, utilizing data from the Environmental Health Risk Assessment and the Master Plan for Wastewater Management Systems (RISPAL), as well as the results of Focus Group Discussions. A strengths, weaknesses, opportunities, and threats (SWOT) analysis was used for strategy formulation. Meanwhile, the method of overlaying thematic maps of sanitation risk, extreme poverty, and stunting was used to determine priority intervention locations. The research identified several key multidimensional barriers including social factors, such as low public awareness regarding the importance of regular septic tank pumping; financial constraints, due to the perceived high cost of pumping service and limited operational budget; infrastructure gaps including inadequate fleet logistics and limited service coverage of fecal sludge treatment plants (FSTP); and policy constraints, such as the absence of supporting regulations concerning service fees. The findings recommend an aggressive strategy translated into short, medium, and long-term action plans, focusing on the phased construction of seven new FSTPs, strengthening regulatory frameworks, and raising public awareness in priority areas to achieve sanitation targets and sustainably.